PERGESERAN PEMIKIRAN NEGARA KESEJAHTERAAN PASCA AMANDEMEN UUD 1945 - Djauhari . (Jurnal Pembaharuan Hukum, 2014)
The amendment process of Article 33 Constitution 1945 caused push and pull of thinking, necessary or not to be amended, so there are two groups which are pro’s and con’s diametrically. This amendment produced two additional paragraph in Article 33, which is formely two paragraph became five paragraphs, those are pragraph (4) and paragraph (5), are the system of welfare, especially in the economic sector, accepted the positive side from liberalism and socialism system,but rejected market fundamentalism. Apparently the concept of Welfare State is confirmed in the additional of social-economic articles, namely in Article 34 paragraph (2) and paragraph (3).